The influence of squeegee parameters on ink deposit in UV halftone screen printing - Eifion Jewell (TAGA Journal., 2006)
Screen printing with high build UV inks is prone to excess ink transfer (stacking) or insufficient ink transfer (skipping) in the second, third and fourth colours due to the rough surface provided by the first ink layer. An experimental investigation into the effect of squeegee material and squeegee pressure on the second colour ink transfer was undertaken using an innovative experimental technique. The technique involved printing the magenta ink at various press conditions through the magenta screen on top of a colourless base material through the yellow screen. Differences in the print density of the magenta as a result of squeegee material and pressure are then associated with changes in the magenta ink density only. Squeegees of 75 and 84 shore “A” hardness were used to print a conventional UV ink at 5 pressures from 2.5 to 4.5 bar on a poster and silk substrate. For halftone printing the degree of stacking was almost linearly related to the applied squeegee pressure, increasing the second colour density in a stepwise manner. The effect was most noticeable in the second colour mid tones and was greatest when the first “colour” was between 40% and 70%. An appreciable increase in ink density was also visible when the second colour solid was printed on any halftone or solid layer. This can in part be attributed to the base material acting like a transparent material. As the ideal conditions for limiting skipping / stacking varies with the percentage of the first colour printed, it is likely that this phenomena is present in all 4 colour UV screen printing. The findings are also relevant for the printing of multi layer fine lines and solid areas.